Нагляд прокурора за додержанням законів під час проведення досудового розслідування: тенденції нормотворення та правозастосування - Чорноусько, М.; Chornousko, М. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглядаються деякі питання нагляду прокурора за додержанням законів під час проведення досудового розслідування. Здійснюється аналіз чинного національного та міжнародного кримінального процесуального законодавства, справ, розглянутих Європейським судом з прав людини, точок зору науковців з приводу ключових аспектів діяльності прокурора в конкретному кримінальному провадженні. Подається виклад сучасних тенденцій нормотворення та правозастосування, заснований на існуючих законодавчих ініціативах, висновках практиків щодо недоліків нормативної бази та даних офіційної статистики відповідно. Пропонується авторська класифікація проблем, що виникають в контексті наглядової діяльності прокурора у кримінальному провадженні. The article considers certain problematic issues of implementing prosecutor’s supervision over the observance of laws in the course of pre-trial investigation. Modern tendencies of rule-making and Laws enforcement have been studied on the basis of available legislative initiatives, practitioners’ conclusions as to the shortcomings of the current regulatory framework, official court and prosecution statistics. The article analyzes the importance of the general principles of criminal proceedings in the prosecutor’s performance of supervisory activities in the process of pre-trial investigation. The article offers author’s classification of common debatable questions arising in the process of prosecutors supervision activities and introduces some important proposals for editing the criminal procedural code, among which those aimed at ensuring the rights of the participants of the criminal proceeding, optimization of the established principles of the equality of the parties to proceedings in accordance with the doctrinal standards and practice requirements. The article offers the ways to reduce the workload on the prosecutors.
Prosecutor’s supervision over the observance of laws in the course of pre-trial investigation: tendencies in rule-making and laws enforcement
Keywords: нагляд прокурора; повноваження прокурора; досудове розслідування; класифікація проблем; забезпечення прав; правозастосування; prosecutor’s supervision; prosecutor’s power; pre-trial investigation; classification of problems; ensuring the rights; laws enforcement